ADMA and NT pro‐BNP are associated with overall mortality in elderly. (16th November 2018) - Sheikh Rezaei, Safoura; Weisshaar, Stefan; Litschauer, Brigitte; Gouya, Ghazaleh; Ohrenberger, Gerald; Wolzt, Michael
Abstract: Background: Increased asymmetrical dimethylarginine (ADMA) and NT pro‐BNP concentrations have been associated with mortality in patients with cardiovascular (CV) disease and the general population. The use of these prognostic markers in an older population is not established yet. The aim of the present study was to investigate the prognostic value of age, sex, BMI, co‐medication and CV laboratory risk markers in geriatric care patients. Materials and methods: In this prospective observational single‐centre cohort study data of long‐term geriatric care patients were collected. Blood samples were collected between 14.09.2009 and 16.12.2009, and mortality was recorded up to 90 months. ADMA, its symmetric isomer SDMA, L‐arginine, NT pro‐BNP and CRP were determined at study entry. Simple associations of risk factors for survival period were explored by Spearman correlation coefficient. Significant univariate predictors for survival period were used in the Cox proportional hazard model. Results: A total of 481 patients were screened, and data from 449 patients were analysed. A total of 381 patients died during the observation period. Full data sets from 344 patients were used for Cox regression analysis. Male sex, older age, lower BMI, use of neuroleptic medicine, peripheral artery disease, and elevated plasma concentrations of ADMA, NT pro‐BNP, and CRP were significant predictors of mortality. Conclusion: The concentration of ADMA and NT pro‐BNP may be used as an early risk marker for overall mortality in geriatric care. Neuroleptic medicine is associated with increased mortality in this population.